Both Reaction Time and Accuracy Measures of Intraindividual Variability Predict Cognitive Performance in Alzheimer's Disease - Christ, Björn U.; Combrinck, Marc I.; Thomas, Kevin G. F. (Frontiers in Human Neuroscience, 2018)
Dementia researchers around the world prioritize the urgent need for sensitive measurement tools that can detect cognitive and functional change at the earliest stages of Alzheimer’s disease (AD). Sensitive indicators of underlying neural pathology assist in the early detection of cognitive change and are thus important for the evaluation of early-intervention clinical trials. One method that may be particularly well-suited to help achieve this goal involves the quantification of intraindividual variability (IIV) in cognitive performance. The current study aimed to directly compare two methods of estimating IIV (fluctuations in accuracy-based scores versus those in latency-based scores) to predict cognitive performance in AD. Specifically, we directly compared the relative sensitivity of reaction time (RT) - and accuracy-based estimates of IIV to cognitive compromise. The novelty of the present study, however, centered on the patients we tested (a group of patients with Alzheimer’s disease (AD)) and the outcome measures we used (a measure of general cognitive function and a measure of episodic memory function). Hence, we compared intraindividual standard deviations (iSDs) from two RT tasks and three accuracy-based memory tasks in patients with possible or probable Alzheimer’s dementia (n = 23) and matched healthy controls (n = 25). The main analyses modeled the relative contributions of RT versus accuracy-based measures of IIV toward the prediction of performance on measures of (a) overall cognitive functioning, and (b) episodic memory functioning. Results indicated that RT-based IIV measures are superior predictors of neurocognitive impairment (as indexed by overall cognitive and memory performance) than accuracy-based IIV measures, even after adjusting for the timescale of measurement. However, one accuracy-based IIV measure (derived from a recognition memory test) also differentiated patients with AD from controls, and significantly predicted episodic memory performance. The findings suggest that both RT- and accuracy-based IIV measures may be useful indicators of underlying neuropathology. The present study therefore contributes toward an understanding of the relative utility of RT- and accuracy-based IIV measures in detecting neurocognitive impairment in older adults, and also advances the empirical evaluation of sensitive markers of cognitive change in patients with AD.